(untitled) (Journal of actual problems of jurisprudence, 2020)
This article is devoted to the legal analysis of external security of the Republic of Kazakhstan. It also explores various approaches to the study of external security in accordance with the Kazakh legislation and legal standards of foreign countries. The article considers the scientific positions of scientists that they set out in the process of conducting fundamental research. Currently, the Republic of Kazakhstan has a fairly extensive security system. This article is devoted to the legal analysis of the state’s activities in the field of external security. There are both theoretical and practical problems in this area. Ensuring external security requires a special approach to the legal regulation of this sphere. Thus, a single conceptual framework has not yet been developed. It should also be noted that the issues of administrativelegal regime need to be solved through which in fact a degree of ordering has achieved as the system of external security and its components and individual processes in the field of security of individuals, society and the state. Key words: national security, ensuring security, external security, the Constitution, law, threats to external security.